Ahmed Glaucoma Valve Implantation for Refractory Glaucoma in a Tertiary Hospital in Brazil - Ricardo Yuji Abe; Carla Melo Tavares; Rui Barroso Schimiti; José Paulo Cabral Vasconcellos; Vital Paulino Costa (Journal of Ophthalmology)
Purpose. To evaluate the efficacy of Ahmed Glaucoma Valve (AGV) implantation in patients with refractory glaucoma in a tertiary hospital in Brazil. Methods. Retrospective case series of patients who underwent AGV implantation. Primary outcome was to assess the rate of failure, which was defined as intraocular pressure (IOP) in two consecutive visits greater than 18 or lower than 5 mmHg (criterion 1) or IOP greater than 15 or lower than 5 mmHg (criterion 2). The secondary outcome was to investigate risk factors for failure. Results. 112 eyes from 108 patients underwent AGV implantation between 2000 and 2012. Mean follow-up time was 2.54 (±1.52) years. Kaplan-Meier survival analysis showed cumulative probabilities of success of 80.3%, 68.2%, and 47.3% at 1, 3, and 5 years using 18 mmHg as endpoint. When adopting 15 mmHg as endpoint, cumulative success rates were 80.3%, 60.7%, and 27.3% at 1, 3, and 5 years, respectively. Multivariate analysis with generalized estimating equations revealed that African American ancestry and early hypertensive phase were risk factors for failure (P=0.001 and P=0.002, resp.). Conclusion. A success rate of approximately 50% was obtained 5 years after the implantation of an AGV. African American ancestry and early hypertensive phase were associated with increased risk of failure.